An Azimuth-Based Dead-End Avoiding Routing Mechanism for Providing Reliable IP Connectivity in Multihop Wireless Networks - Hyun Yu; Sanghyun Ahn (International Journal of Distributed Sensor Networks)
In a multihop wireless network, such as a wireless sensor network (WSN), with nodes being aware of their locations, the geographic routing scheme is an effective way of delivering packets to their destinations because of its 1-hop beacon broadcasting based routing related information exchange operation. The routing information obtained via 1-hop beaconing is local in the sense that it is just 1-hop compared to the multihop end-to-end routing. Hence, at some point, packets may experience no more place to be forwarded to (i.e., dead-ends). In this paper, we propose a geographical routing mechanism adopting the concept of the azimuth to reduce the possibility of packets confronting dead-ends. In other words, the node with a packet to be forwarded to the final destination figures out the next-hop node by utilizing the azimuth of the destination as a routing metric. Besides, we propose additional routing metrics for stable next-hop node selection to provide reliable IP connectivity. In order to validate the performance of the proposed routing mechanism, we evaluate its performance through the NS-2 based simulations and show that our mechanism outperforms the other schemes in terms of the packet delivery success rate, the end-to-end delay, and the number of dead-end encounters.